Postawy Polaków wobec Żydów w Generalnym Gubernatorstwie na wybranych przykładach - Rączy, Elżbieta (Polityka i Społeczeństwo, 2020)
The article describes the attitudes of Poles towards Jews during the occupation of Poland by Nazi Germany. The examples provided in the article show how much these attitudes varied. On the one hand there was Poles’ spontaneous and heroic fight for the lives of those who escaped from ghettos, which sometimes resulted in the death of those hiding and those who aided them, on the other hand there was the plunder of Jewish property and denunciations, roundups and murders of Jews. The article also shows how far the war reality determined the attitudes of individual Poles towards Jews. Sometimes they had to choose between their own safety or even lives and the lives of others. It happened that they rescued some Jews and some they denounced to the Germans. The article proves that the attitudes of Poles towards the Jewish population, which are often described as black-and-white, were altogether not so unequivocal.